Overcoming Speech Anxiety in English Language Classrooms - Kuswantoro, Avinda Virnadya; Novita, Dian (Pubmedia Jurnal Pendidikan Bahasa Inggris, 2024)
This study investigates the impact of anxiety indicators on the speaking abilities of students in a bilingual junior high school setting, focusing on the challenges faced in English language usage within the classroom. Employing qualitative descriptive methods, including observations and interviews, the research encompassed 27 students and one English teacher. The analysis identified two predominant forms of anxiety affecting the students: a fear of making mistakes and a lack of self-confidence, which notably impaired their interaction in English with peers and educators. The study suggests implementing "English Day" activities as a strategic intervention to reduce linguistic anxiety and promote language skills, thereby improving students' communicative performance in English. This approach holds implications for enhancing language acquisition strategies in bilingual educational contexts.